113 Comparison of Collagenase Clostridium Histolyticum to Surgery for the Management of Peyronie's Disease: A Randomized Trial. (1st May 2022) - Green, B; Francis, M; Savage, J; Brearton, K; Burgon, H; Tyler, A; Trost, L
ABSTRACT: Introduction: Since the FDA approval of Collagenase Clostridium Histolyticum (CCH) for the treatment of Peyronie's Disease (PD), there has been significant debate as to its role and comparable efficacy in relation to surgical therapies. Specifically, investigators have compared relative utilization, costs, and outcomes with varying conclusions. Objective: To compare various objective and subjective outcome measures between men undergoing CCH or surgery for PD. Methods: A randomized, controlled trial (NCT04786106) is ongoing at ***. Participants are randomized 1:1 to receive either CCH + traction (RestoreX) + sildenafil or penile surgery (plication and/or incision and grafting) + traction + sildenafil for PD. Objective, standardized (International Index of Erectile Function [IIEF] and Peyronie's Disease Questionnaire [PDQ]), and non-standardized assessments are obtained at baseline, and post-treatment at 3, 6, 12, 24, 36, 48, and 60 months. Key outcomes include differences in standardized questionnaires, penile curvature, penile length, subsequent interventions, and non-standardized questionnaire responses. Curvature is measured in two planes and summed to provide a composite curvature. Penile length is measured from pubic symphysis to corona. All therapies were stopped prior to the 3-month time point (i.e. traction and sildenafil). Results: A total of 32 men have been randomized to date (CCH=17, surgery=15), with 3-month data available on 8 men (CCH=4, surgery=4). Mean age at enrollment was 55.8 years (SD 14.4), PD duration 38 months (SD 49.5), curvature 74.1 degrees (SD 20.9), and penile length 12.5 cm (SD 1.5). All baseline variables were statistically similar between cohorts. Regarding the primary outcome, at 3 months post-treatment, CCH men reported higher overall satisfaction (not statistically significant; 50% very satisfied, 50% somewhat satisfied; surgery 100% somewhat satisfied, p=0.06). For secondary outcomes at 3 months, the median differences between CCH and surgery respectively were: IIEF-EFD (+4 vs +4, p=1.0), PDQ-physical (-10 vs -6.5, p=0.14, note: lower is better for PDQ scales), PDQ-pain (-12 vs 0.5, p=0.77), PDQ-bother (-9 vs -8, p=0.77), length change (+0.8 vs 0 cm, p=0.29), curvature absolute change (-22.5 vs -80 degrees, p=0.11), and curvature percentage improvement (41% vs 85%, p=0.11). An equal number of CCH and surgery men felt that treatment improved sexual function (75%) and their ability to have sex (100%) and were subjectively happy with their curvature (50%). Men in the surgery arm were more likely to report (note that some are not statistically significant) subjectively worsened erectile function (50% vs 0%, p=0.15), shorter penile length (75% vs 0%, p=0.02), lower satisfaction with penile length (50% satisfied vs 75%, p=0.46), improved hourglass (33% vs 0%, p=0.42), and were less likely to report that they would repeat treatment without reservation (50% vs 75%, p=0.11). When asked which treatment they would pick if they could start again, 100% of CCH men reported CCH and/or traction, while 50% of surgery men indicated surgery, 25% CCH, and 25% other (p<0.05). Conclusions: The current data are too preliminary to draw any viable conclusions on differences between CCH and surgery for PD. Disclosure: Work supported by industry: yes, by Endo Pharmaceutical.